Evaluation of pharmacological therapies used in Costa Rica in patients with metastatic gastric cancer: a retrospective study - Cordero García, Ana Eugenia (2019)
Background: Gastric cancer is one of the leading causes of cancer death worldwide. Surgery is regarded as the best curative treatment option for gastric cancer; however, a high proportion of cases are diagnosed at advanced stages, when tumors are unresectable. In the present study, we evaluated the impact of pharmacological therapies in the survival of 168 patients diagnosed with metastatic gastric cancer from Costa Rica, a country with very high incidence and mortality rates for this malignancy. Methods: We retrospectively reviewed 168 clinical records of patients diagnosed with metastatic gastric cancer from January 2009 to January 2012 at four major hospitals in Costa Rica. The Chi-square test or Fisher’s exact test was used for comparison of frequencies, while the ANOVA test was used for comparison of quantitative variables. OS and PFS analyses were performed using the Kaplan-Meier method. The Log-rank test was used to compare survival curves. Univariate and multivariate COX regression analyses were used to calculate the crude and adjusted hazard ratios (HR) with their 95% confidence interval (95% CI). Results: After a median follow-up of 46.5 months, the median survival difference between the two groups (pharmacological therapy vs. supportive care) was 5.6 months for PFS and 8.3 months for OS. Patients receiving triple therapy had 69% higher chance of progression than those receiving double therapy (HR =1.69, 95% CI: 1.04–2.73). The probability of dying is 88% higher for the patients receiving triple therapy than for those using double therapy (HR =1.88, 95% CI: 1.15–3.11). Conclusions: This study demonstrates that pharmacological therapies significantly increase the PFS and OS of those patients with metastatic gastric cancer in Costa Rica. The greatest benefit in terms of survival is observed with the use of duplets in comparison with the triplets in these patients.